Pemanfaatan Online Public Access Catalog (OPAC) Untuk Meningkatkan Kualitas Layanan di Perpustakaan Universitas Negeri Padang - Mawati, Yanis; Nst., Bakhtaruddin (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper focuses on the use of online public access catalog (OPAC) to improve the quality of library services at the State University of Padang. The purpose of this paper is (1) to describe the use of OPAC in the library of the State University of Padang and (2) describe any obstacles encountered in the use of OPAC in the library of the State University of Padang. This type of research used in this study is a qualitative research through observations and interviews.Based on analyzing the data can be summarized as follows: first, the use of the library OPAC in Padang State University have not been fully utilized by the users effectively and efficiently. Second, the constraints faced in the use OPAC at the State University of Padang is the lack of supporting facilities such as computer software, which is used OPAC user not friendlysehingga bit difficult for users to process information retrieval, and information presented in the OPAC are still not complete. That the use of OPAC in information retrieval can be done well, and can be reused as much as possible is recommended; Should Padang State University library in tackling problems in the use of the OPAC is to add facilities such as computers, giving guidance or direction to users on how to use OPAC ; Padang State University Library must make improvements to the field of information services that provide complete information. Keywords: online catalog, library, catalogue